Parasites under pressure: salmon lice have the capacity to adapt to depth-based preventions in aquaculture. Issue 10 (September 2020) - Coates, Andrew; Phillips, Ben L.; Oppedal, Frode; Bui, Samantha; Overton, Kathy; Dempster, Tim
Graphical abstract: Highlights: Salmon louse copepodids adjust swimming behaviour in response to changes in hydrostatic pressure. The pressure response differs between salmon louse families. There is a significant effect of family on the vertical distribution of copepodids in the water column. Abstract: The evolution of pesticide resistance has driven renewed interest in non-chemical pest controls in agriculture. Spatial manipulations (physical barriers and fallowing, for example) can be an effective method of prevention, but these too might impose selection and cause rapid adaptation in pests. In salmon aquaculture, various non-chemical approaches have emerged to combat parasitic salmon lice ( Lepeophtheirus salmonis ) – a major pest with clear signs of evolved chemical resistance. 'Depth-based' preventions, now widely implemented, reduce infestation rates by physically segregating salmon from lice in their infective copepodid stage occurring in surface waters. Copepodids distributed deeper in the water column, however, can bypass these barriers and infest farms. If swimming depth is a heritable trait, we may see rapid evolutionary shifts in response to widespread depth-based prevention. We collected lice from Norwegian salmon farms and assayed more than 11, 250 of their laboratory-reared offspring across 37 families. The vertical distributions of copepodids were measured using experimental water columns pressurised to simulate conditions at 0, 5 and 10 m depths. We demonstrated that lice respond strongly to hydrostatic pressure: an increase in pressure doubled the number of lice that migrated to the top of columns. There was also a large effect of family on this response, with the percentage of lice ascending to the top of pressurised columns ranging from 17 to 79% across families. Families with a weak swimming response to pressure are expected to occur deeper in the water column and so be more likely to infest farms employing depth-based preventions. If this between-family variation reflects genetic variation, then the parasite population may have the capacity to adapt to preventative measures. Such adaptation would have important commercial and ecological implications.